NCOG-29. INFLUENCE OF RADIATION DOSES TO HIPPOCAMPAL SUBVOLUMES ON MEMORY OUTCOMES IN PITUITARY TUMORS: DOES THE ENTIRE HIPPOCAMPUS NEED TO BE SPARED?. (14th November 2022) - Dasgupta, Archya; Thomas, Ajay; Sahu, Arpita; Agarwal, Ujjwal; Chatterjee, Abhishek; Goswami, Savita; Gaikwad, Utpal; Singh, Vikas; Shetty, Prakash; Moiyadi, Aliasgar; Sahay, Ayushi; Sridhar, Epari; et al.
Abstract: INTRODUCTION: In patients treated with radiation (RT), doses to hippocampus influence neurocognitive outcomes. However, the role of hippocampal subvolumes in memory functioning has not been reported, which prompted the current study. METHODS: Adults ( > 18 years) with pituitary tumors treated with fractionated RT (45 Gy/ 25 fractions/ 5 weeks) were accrued in the prospective study. Hippocampus was delineated on T1-weighted 3D-FSPGR sequences with 1mm slice thickness. The head, body, and tail of hippocampus were drawn for the current study based on the consensus of two neuroradiologists. The anatomical landmarks were: head (basilar artery to interpeduncular cistern), body (interpeduncular cistern to superior colliculus), and tail (beyond superior colliculus). Memory assessment was done pre-RT and 18 months post-RT by dedicated neuropsychologist using Weschler Memory Scale. The dose-volume parameters (maximum, mean, D10-D100) were extracted from bilateral hippocampus and subvolumes individually, which were correlated with the memory outcomes. Binary endpoints of > 5% drop of memory quotient (MQ) or not at 18 months were used for analysis using an independent t-test or Mann Whitney test as appropriate. RESULTS: Of 25 patients included in the analysis, 11 had drop of MQ > 5% at 18 months. The left and right hippocampus doses of D10, D20, and D30 were significantly higher in patients with higher memory decline. For the subvolumes, only dose to bilateral head had statistically significant impact on MQ. Mean doses for patients with > 5% MQ drop for left and right heads were 26 Gy and 24 Gy compared to 21 Gy and 19 Gy, respectively, for the other group. CONCLUSION: Doses to bilateral hippocampus were shown to impact short-term memory. Of the subvolumes, only head appeared significant in memory functioning from the current pilot study, opening a window for exploring stricter dose constraints towards hippocampal head for primary or metastatic brain tumors.